(untitled) (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2026)
Background and Aim. Mental health literacy is closely related to health behaviour factors that strongly affect adolescent wellbeing. Physical activity, sleep and screen time are consistently linked to adolescents’ mental health. This study aimed to assess the mental health literacy of 9th–10th grade students and its associations with their health behaviours. Methods. A cross-sectional study was conducted among 847 pupils aged 14–17 years (mean 15.40 (0.60)) from the Kaunas district, studying in grades 9 and 10; 55.4% were girls. Mental health literacy was assessed using the Mental Health Literacy Questionnaire (MHLq). Data on health behaviours, including physical activity, sleep duration, and screen time, as well as sociodemographic variables, were collected using standardised questionnaires based on national methodological recommendations. Results. The overall mental health literacy score was 127.61, with girls scoring 130.33 and boys 123.83. Girls, older students, and those with higher social status had significantly higher mental health literacy scores (p < 0.001). Weekly physical activity was significantly predicted by sex (β = –0.23; p < 0.001), socio-economic status (β = 0.18; p < 0.001), and mental health literacy (β = 0.07; p = 0.04). Sleep duration on school days was predicted by sex (β = –0.25; p < 0.001) and mental health literacy (β = 0.09; p = 0.01). Screen time on school days was predicted by sex (β = 0.11; p = 0.01), socio-economic status (β = –0.11; p = 0.01), and mental health literacy (β = –0.16; p < 0.001), with higher mental health literacy associated with less screen time. Conclusions. Higher mental health literacy among 9th–10th grade students is associated with more favourable health behaviours, including higher physical activity, longer sleep on school days, and reduced screen time. The results underline the need for school-based initiatives to strengthen mental health literacy, particularly among boys, younger students, and adolescents from lower socio-economic backgrounds. Keywords: Mental health literacy; adolescence; health behaviour